An interactive computer-based learning using internet for electrical engineering student (synchronous generator) / Abdul Rahman Minhat - Minhat, Abdul Rahman (2001)
This report describes an Interactive-Computer-Based Learning (ICBL) system using the Internet, which is developed for electrical engineering student in higher educational center. The platform of ICBL is to use the website technique for improving the conventional learning by providing interactive notes, animated graphics, working examples, feedback form and quiz through the web.